2016
DOI: 10.1007/s00214-016-1991-9
|View full text |Cite
|
Sign up to set email alerts
|

Spin polarization in SCC-DFTB

Abstract: We evaluate the performance of spin-polarized DFTB within the SCC-DFTB (also known as DFTB2) model. The method has been implemented in the ADF modeling suite. We briefly review how spin polarization is incorporated into the DFTB2 method and validate the method in terms of structural parameters and energy using the GMTKN30 test set, from which we used 288 spin-polarized systems.Comment: The final publication is available at Springer via http://dx.doi.org/10.1007/s00214-016-1991-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The presence of the layer was found to reduce by one order of magnitude the current with respect to the free surface, in agreement with experimental data [327]. Monolayers (OH, HS and S) were also added in a DFTB study of the sulfidization-amine flotation mechanism of smithsonite in order to model the hydration effect of water and the sulfidization effect on the ZnCO 3 (101) surface [328]. The structural study of a water monolayer on oxide surfaces has led to several DFTB studies, for example on ZnO [329], on a TiO 2 anatase surface [330] or on an alumina surface on which it has been found that water dissociates rapidly, leading to an -OH group coverage of about 4.2 groups/nm 2 [331].…”
Section: Supported or Embedded Systemssupporting
confidence: 79%
See 1 more Smart Citation
“…The presence of the layer was found to reduce by one order of magnitude the current with respect to the free surface, in agreement with experimental data [327]. Monolayers (OH, HS and S) were also added in a DFTB study of the sulfidization-amine flotation mechanism of smithsonite in order to model the hydration effect of water and the sulfidization effect on the ZnCO 3 (101) surface [328]. The structural study of a water monolayer on oxide surfaces has led to several DFTB studies, for example on ZnO [329], on a TiO 2 anatase surface [330] or on an alumina surface on which it has been found that water dissociates rapidly, leading to an -OH group coverage of about 4.2 groups/nm 2 [331].…”
Section: Supported or Embedded Systemssupporting
confidence: 79%
“…where index l μ indicates the shell associated with orbital μ on a given atom. Note that Melix et al [101] use a version resolved to atoms only where the spin-polarized DFTB energy is…”
Section: Spin-polarized Dftbmentioning
confidence: 99%
“…[130] Most widely applied parameters include the mat-sci parameters for DFTB0, [131] the mio parameters for SCC-DFTB, and more recently the 3ob [132] parametrization, applicable to DFTB2 and DFTB3. Spin polarization [133,134] and spin-orbit coupling (SOC) [135] can also be included. London dispersion interactions are commonly treated using an a posteriori correction [136,137] or the manybody dispersion (MBD) approach.…”
Section: Methodsmentioning
confidence: 99%
“…[132] Most widely applied parameters include the mat-sci parameters for DFTB0, [133] the mio parameters for SCC-DFTB, and more recently the 3ob [134] parametrization, applicable to DFTB2 and DFTB3. Spin polarization [135,136] and spin-orbit coupling (SOC) [137] can also be included. London dispersion interactions are commonly treated using an a posteriori correction [138,139] or the many-body dispersion (MBD) approach.…”
Section: Dftbmentioning
confidence: 99%